An experimental study on the thermal performance of mixed phase change materials-based battery cooling system. (February 2022) - Liu, Jiahao; Fan, Yining; Xie, Qimiao
Highlights: The concept of mixed phase change materials (PCMs) is experimental investigated. The mixed PCMs can improve the cooling efficiency of the PCM-based system. The cooling performance of mixed PCMs depends on their mixing ratio. The ambient temperature greatly affects the cooling efficiency of the mixed PCMs. Abstract: Phase change materials (PCMs) have been widely used in the battery thermal management system (BTMS) due to their excellent cooling efficiency. Previous studies mainly focused on the effect of pure PCM with onefold phase change temperature (PCT) on cooling the battery, while the battery temperature generally varies in a wide range, especially under abuse conditions, which tends to cause the underutilization or exhaustion of the latent heat of the PCM. This paper experimentally investigates the thermal performance of mixed PCMs with different PCTs (37 and 58 ℃, i.e. PCM-37 and PCM-58) by means of a laboratory-scale PCM-based battery cooling system, seeking to obtain the optimal mixing ratio at various ambient temperatures (30, 40, 50 ℃). The experimental results show that the cooling performance of the mixed PCM is satisfying, especially at the ambient temperatures of 30 ℃ and 40 ℃, where the optimal proportion of (PCM-37: PCM-58) is 3:1 and 1:3, respectively. However, at 50 ℃, the pure PCM-58 exhibits the best cooling effectiveness, since the latent heat of PCM-37 is exhausted at high ambient temperature, and the presence of PCM-37 will weaken the heat dissipation effect. The findings above quantitatively demonstrate the advantage of mixed PCMs on cooling the cycling battery at elevated ambient temperatures. In light of the temperature sensibility of PCM, this work provides a novel insight into the improvement of PCM-based BTMSs.